Protective Effect of High-Intensity Interval Training (HIIT) and Moderate-Intensity Continuous Training (MICT) against Vascular Dysfunction in Hyperglycemic Rats - Nurul Paramita; Brilliant C. Puspasari; Randika Arrody; Neng T. Kartinah; Trinovita Andraini; Julfiana Mardatillah; Hardiyanti Rusli; Dewi I. S. Santoso (Journal of Nutrition and Metabolism)
Background. Hyperglycemia is a major risk factor for endothelial dysfunction. Endothelial dysfunction is associated with the inability of endothelial cells to maintain homeostasis of the cardiovascular system. Regular exercise may be considered as an effective and low-cost nonpharmacological tool for improving vascular function, though there is no agreement on the best type of exercise. Objectives. To determine how high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) may prevent endothelial dysfunction under hyperglycemic conditions, and to compare these two interventions. Method. Twenty-four eight-week-old male Wistar rats were randomly assigned into four groups: healthy nonexercising control (C), hyperglycemic control (HG-C), hyperglycemic + HIIT (HG-IT), and hyperglycemic + MICT (HG-CT). Hyperglycemia was induced by a single injection of streptozotocin. Hyperglycemic animals were subjected to HIIT or MICT protocols six days a week for six weeks. Decapitation was performed the day after the exercise protocols were completed. The ascending aorta (until the abdominal artery) was examined. An enzyme-linked immunosorbent assay (ELISA) was used to measure the glucagon-likepeptide-1 (GLP-1), endothelial nitric oxide synthase (eNOS), and tumor necrosis factor-alpha (TNFα) levels. A colorimetric assay was used to measure superoxide dismutase (SOD) activity and malondialdehyde (MDA) levels. Quantitative real-time polymerase chain reaction (PCR) was used to measure the expression of the receptor for advanced glycation end-products (RAGE) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). Hematoxylin and eosin (H&E) staining was used to histologically analyze the aortas. Results. There was a significantly higher level of GLP-1 and lower expression of RAGE, NF-κB, and TNFα in the HG-IT and HG-CT group compared to the HG-C group. Microscopic examination of aortic tissue showed a better tissue arrangement in both treatment groups than in the HG-C group. Except for the MDA level, there were no significant differences in any of the measured parameters between the HG-IT and HG-CT groups. Conclusion. Under hyperglycemic conditions, both HIIT and MICT have a protective role against endothelial dysfunction.